Regimes of happiness: comparative and historical studies - Contreras-Vejar, Yuri; Jen, Joanna Tice; Turner, Bryan S. (Anthem Press, 2019)
"Regimes of Happiness" is a comparative and historical analysis of how human societies have articulated and enacted distinctive notions of human fulfillment, determining divergent moral and ethical traditions and incommensurate and conflicting understanding of the meaning of the "good life.'"-- Provided by publisher.